Proposed Marketing Strategy to Enhance Customer Retention for PT Eldira Fauna Asahan - Adelia Nabilah Setiawan; Atik Aprianingsih (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
In business-to-business firms that are in the commodity markets with limited product differentiation, customer retention is very crucial. This study studies customer purchasing behavior and retention variables in the industry North Sumatra livestock industry by the case study of PT Eldira Fauna Asahan which is cattle fattening company that has gone through a five-year period of fifty five percent sales decline even though product and price remained the same. Using qualitative case study as the research method, semi-structured interviews were carried out on five business customers and three employees of the company to learn about the process of organizational buying decisions in the eight-stage business buyer decision process. The Service Quality Gap Model analysis indicates that the main cause of customer attrition is the inconsistency of service delivery at the peak periods and not the product or price quality. Customers stated high satisfaction with the quality of cattle and price competitiveness although the level of service declined with high levels due to delays in communication, facing uncertainty to coordinate delivery and to be responsive to customers when staff capacity became limiting. Internal analysis reveals that there is a lack of customer service expectations, lack of standard service protocols and reactive operation methods in the management that create gaps in the services that undermine customer trust. The study suggests a holistic approach, which has four priorities: organized communication channels with four-hour turnaround guarantees, relationship reinforcement through periodic business reviews and selective payment options, scheduling reliability through structured schedules, and customer recovery through individual customer outreach. The implementation is aimed at achieving ninety-five percent retention rate, 90 percent on time delivery, and 20 percent growth in revenues in eighteen months. The study adds empirical support showing the impact of dimensions of service quality on buyer decision making in an organization and retention of customers in agricultural supply chains where there is trust in relationships and product differentiation is low.